Perceptions of Portuguese University Teachers About Critical Thinking Educational Practices - Morais, Felicidade (2019)
Promoting students’ Critical Thinking (CT) in Higher Education Institutions (HEI) has been an essential and challenging goal in the 21st century. This exploratory research study attempted to characterize how CT is being fostered in Portuguese HEI. Semi-structured interviews were carried-out with 5 university teachers from different domains, focusing several topics: CT notion, CT aims, CT approach, interventions, teaching strategies, learning materials, assessment methods, challenges and barriers. Results highlighted the undervalue of CT dispositions by university teachers, the lack of clarity regarding the design principles and criteria behind effective CT instruction and assessment, and the need to change institutional culture and conditions towards the support of CT educational practices – this will also enable the long-term integration of CT across the curricula and the transferability of skills and dispositions to other contexts. In general, teachers agreed on the importance to be explicit and clear in their CT teaching practice, and on the use of authentic situations, dialogue and active learning strategies for the effective development of students’ CT.